Deformation Of L-Shaped Aerospace Composite Components - Mohd Sanusi, Mohammad Hamdan (2017)
Advanced composite materials are increasingly selected to be used in fabricating new generation of aircraft primary structures than traditional materials due to its high strength-to-weight ratio, fatigue and corrosion resistance. Despite the rapid rising of the composite usage in aircraft industry recently, composite structures depict process-induced geometrical and dimensional distortion after processing. The shape deformation is unpredictable and contributes a mismatch between assembled components. Often, a traditional trial-and-error approach is deployed iteratively to ensure manufacturability in the mass production, which is very uneconomical, expensive and time consuming. There is still lacking experimental data and studies on the effect of different weaving styles of plain weave (PW), 5 harness satin (5HS) and 8 harness satin (8HS) in affecting shape deformation of angled composite laminates. The composite material selected was carbon fibre reinforced with epoxy matrix that could be cured at elevated temperature of 180°C with 7 bars pressure in the autoclave. Using design of experiment (DOE) methodology, two-level fractional factorials of 24-1 Resolution IV were performed to investigate the main effects and interactions of different plies orientation, number of layers, sample sizes, tool materials as well as weaving styles in affecting the spring-in angle of composite laminates. From the design of experiments and analyses of variances, the plies orientation, number of layers, sample sizes and weaving styles were successfully determined to be significant when comparing the effect of PW and 8HS woven fabric. PW fabric induced approximately three times spring-in angle than 8HS. This relationship was determined to be strong with R-squared value of 97.2% and 87.9% when the aluminium and carbon tool was kept constant, respectively. Meanwhile, the relationship of PW and 5HS, and 5HS and 8HS were moderate with an average of R-squared values of 66%. There were some level two interaction terms affecting shape deformation mainly between plies orientation and tool materials when the weaving material was kept constant. On the other hand, the majority of level two interaction terms were between plies orientation and number of layers, and plies orientation and sample sizes when the tool materials were kept constant. Using the actual testing results of coefficient of thermal expansion and chemical shrinkage, the analytical data was calculated and compared with the actual measured results. The coefficient of thermal expansion and chemical shrinkage strain at the through-thickness direction is larger by 10 to 18 times than the in-plane properties dependent of the types of weaving pattern. Unfortunately, the analytical results were not in agreement with the experimental data possibly due to fibres misalignment and slippage during the lay-up process as well as non-thermoelastic properties not taken into account. Despite that, the effect of weaving styles cannot be ignored because statistically there were some main effects and interaction terms that might affect the shape deformation of L-shaped composite laminates.